Circulating multimeric immune complexes contribute to immunopathology in COVID-19 - Jakob Ankerhold; Sebastian Giese; Philipp Kolb; Andrea Maul-Pavicic; Reinhard E. Voll; Nathalie Göppert; Kevin Ciminski; Clemens Kreutz; Achim Lother; Ulrich Salzer; Wolfgang Bildl; Tim Welsink; et al. (Nature Communications, 2022)
During viral infections high levels of antibodies can form soluble immune complexes (sICs) with antigen and trigger Fcγ receptors (FcγR) leading to increased immunopathology. Here the authors measure FcγRs activation by sICs and consider how these may lead to excessive immunopathology during severe SARS-CoV-2 infection.